2010
DOI: 10.2310/6670.2009.00055
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Scanning–Derived Access Volume Flow: Novel Predictor of Success Following Endovascular Repair of Failing or Nonmaturing Arteriovenous Fistulae for Hemodialysis

Abstract: The objective of this study was to evaluate the feasibility of duplex scanning-derived access volume flow (DAVQ) to predict the success or failure of arteriovenous fistulae (AVF) after interventions. Eighty-eight DAVQ measurements were available for 60 AVF in 59 patients. In 25 cases, physical examination findings or inadequate dialysis suggested failing (11) or nonmaturing (14) AVF. Outflow stenoses (1-4; mean 1.2 +/- 0.8) were confirmed by contrast fistulograms in 23 cases (17 peripheral; 6 central). These 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…As currently practiced, the 'access surveillance strategy' uses costly radiology resources and requires significant patient time and inconvenience. 76,79 We need to be able to define and target high risk populations for surveillance, find a validated test to predict those who will succeed or fail after an intervention, 80,81 and determine which interventions will facilitate increased access patency without harm. Targeting measurements to the newest accesses, which are most likely to fail, 50 appears to be a logical step.…”
Section: Current Optionsmentioning
confidence: 99%
“…As currently practiced, the 'access surveillance strategy' uses costly radiology resources and requires significant patient time and inconvenience. 76,79 We need to be able to define and target high risk populations for surveillance, find a validated test to predict those who will succeed or fail after an intervention, 80,81 and determine which interventions will facilitate increased access patency without harm. Targeting measurements to the newest accesses, which are most likely to fail, 50 appears to be a logical step.…”
Section: Current Optionsmentioning
confidence: 99%
“…Duplex derived access volume flow (DAVQ) has been reported by Ascher to be a good predictor of clinical success following endovascular repair of failing or immature access. 29 He found that DAVQ for functioning AAVA's averaged 1199 mL/min. The DAVQ in AAVA's that underwent intervention and went on to become functional for dialysis for at least 6 months was at least 867 mL/min.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical criteria included the inability to achieve prescribed dialysis flow rates and difficulty with cannulation. Other indications included pulsatility (29), low access flow (28), decreased flow (23), infiltration (13), aneurysmal degeneration (11), bleeding (9), pseudoaneurysmal degeneration (6), elevated venous pressures (5), difficult cannulation (3), pain (3), ulceration (1), decreased clearance (1), swelling (1) and decreased arterial pressures (1). More than one indication for intervention was often present in an individual patient.…”
Section: Indicationsmentioning
confidence: 99%
“…Estimates of VFs were based on the mean of at least two congruent measurements in a non-tortuous segment of the brachial artery or in the prosthesis. All interventions were performed with a linear 12 MHz probe (Affiniti 70, Philips Medical Systems) [7]. The interventions were performed in a simple examination room in our outpatient clinic by an experimented angiologist assisted by one vascular nurse.…”
Section: Methodsmentioning
confidence: 99%